2009
DOI: 10.1002/cjs.10019
|View full text |Cite
|
Sign up to set email alerts
|

Variance estimation when donor imputation is used to fill in missing values

Abstract: Donor imputation is frequently used in surveys. However, very few variance estimation methods that take into account donor imputation have been developed in the literature. This is particularly true for surveys with high sampling fractions using nearest donor imputation, often called nearest‐neighbour imputation. In this paper, the authors develop a variance estimator for donor imputation based on the assumption that the imputed estimator of a domain total is approximately unbiased under an imputation model; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Such contradictory phenomena has been discussed by Rosenbaum (1987), Robins et al (1994), Little and Vartivarian (2005), Kim and Kim (2007), Beaumont and Bocci (2009). See also Henmi and Eguchi (2004).…”
Section: Ps Estimationmentioning
confidence: 90%
“…Such contradictory phenomena has been discussed by Rosenbaum (1987), Robins et al (1994), Little and Vartivarian (2005), Kim and Kim (2007), Beaumont and Bocci (2009). See also Henmi and Eguchi (2004).…”
Section: Ps Estimationmentioning
confidence: 90%
“…While we agree that treating the imputed values as if they were observed values tends to lead to variance estimates that are too small (and ultimately to confidence intervals that are too narrow), we believe that this criticism is not justified because it ignores a wide literature on variance estimation procedures for singly imputed data that have been developed in the last two decades in a survey sampling setting, e.g. Rao & Shao (), Särndal (), Shao & Sitter (), Shao & Steel (), Beaumont & Bocci (), Haziza (), Kim & Rao (), among others. Several variance estimation procedures for producing consistent variance estimators are currently available in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…Zhong & Chen () established the consistency of imputed estimators as well as their asymptotic normality for kernel imputation procedures. Theoretical properties of nearest‐neighbour imputation and predictive mean matching can be found in Chen & Shao (), Beaumont & Bocci (), Yang & Kim (), among others. For nearest‐neighbour imputation, Yang & Kim () showed that falsetrueY¯^ItrueY¯=Opfalse(n1false/21false/Gfalse), where G is the number of matching variables.…”
Section: Deterministic Imputation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor imputation is a method in which the missing values for one or more variables of a non responding unit (recipient) are replaced by the corresponding values of a responding unit (donor) with no missing value for these variables. It is a variance estimation method which is valid even in the presence of high sampling fractions [1]. However, very few variance estimation methods that take into account donor imputation have been developed.…”
Section: Introductionmentioning
confidence: 99%